A High‐Speed Camera‐Based Measurement System for the High‐Pressure Entrained‐Flow Gasification. Issue 12 (8th November 2022) - Matthes, Jörg; Kollmer, Max; Eberhard, Mark; Hagenmeyer, Veit; Kolb, Thomas
Abstract: A continuously operated optical measurement system for observation and characterization of the flame structure in an entrained‐flow gasifier operated at 40 bar and 1200 °C is presented. The experimental setup, the image processing system, and the derived parameters for flame characterization are introduced. First results from gasification experiments concerning flame lift‐off distance, flame angle, and flame dynamics are demonstrated. Abstract : An optical measurement system for observation and characterization of the flame structure in an entrained‐flow gasifier operated at 40 bar and 1200 °C is presented. The image processing system and the derived parameters for flame characterization are introduced. First results from gasification experiments concerning flame lift‐off distance, flame angle, and frequency analysis are given.